Preparation of ZnS by magnetron sputtering and its buffer effect on the preferential orientation growth of ITO thin film. (1st April 2018) - Du, Wenhan; Yang, Jingjing; Zhao, Yu; Xiong, Chao
Abstract : Two different deposition sequences were carried to investigate ZnS and indium‐tin oxide (ITO) multiple thin films on quartz substrates using magnetron sputtering technique. In the deposition order of ITO on ZnS layer, ZnS acts as a buffer layer with a thickness of at least 10 nm, and ITO thin film has (222) preferential orientation growth. Besides, lattice constant expansion phenomenon was observed when the film thickness of ITO was increased, indicating tension stress increase in ITO film. The lattice constant mismatch of 5% is the reason for the preferential orientation growth between ZnS and ITO thin films. In the other deposition sequence of ZnS on ITO layer, ZnS thin film has (111) preferential orientation growth. While ITO was kept in multiple crystalline properties. Pinhole‐free ZnS thin film was observed by scanning electron microscopy for this deposition sequential, promising well interface in the thin film solar cells with lower interface defects.